White Light‐Emitting Electrochemical Cells Based on Deep‐Red Cu(I) Complexes. Issue 23 (16th September 2019) - Fresta, Elisa; Weber, Michael D.; Fernandez‐Cestau, Julio; Costa, Rubén D.
Abstract: The synthesis and characterization, as well as photoluminescent and electrochemical features of a series of ionic copper(I) complexes—, i.e., [Cu(N ^ N)(P ^ P)] +, where N ^ N is 4, 4′‐diethylester‐2, 2′‐biquinoline (dcbq) and P ^ P is bis‐triphenylphosphine, bis[2‐(diphenylphosphino)phenyl)ether] (POP), or 4, 5‐bis(diphenylphosphino)‐9, 9‐dimethylxanthene (Xantphos)—are reported along with their application to achieve both deep‐red and white light‐emitting electrochemical cells (LECs). In short, the first deep‐red Cu(I)‐based LECs featuring high irradiances (≈100 µW cm −2 ) and excellent color stability ( x/y CIE color coordinates of 0.66/0.32) over days are reported. This is achieved by comparing the electroluminescent behavior of this series of complexes with respect to the irradiance and stability, as well as the impact of introducing supporting electrolytes on the device performance. This is rationalized using spectroscopic and electrochemical studies. Finally, the first white‐emitting LEC is manufactured with red‐emitting copper(I) complexes, achieving x/y CIE color coordinates of 0.31/0.32 and a high color rendering index of 92. Abstract : The first deep‐red light‐emitting electrochemical cells with [Cu(N ^ N)(P ^ P)] + are reported. Upon increasing the P ^ P rigidity, devices with irradiances of 100 µW cm −2 and stabilities of >150 h are realized. In addition, it is demonstrated how to use a wide bandgap hole transport material to fabricate white‐emitting devices with x/y CIE of 0.31/0.32 and a high color rendering index of 92.